The Role of Myrrh Metabolites in Cancer, Inflammation, and Wound Healing: Prospects for a Multi-Targeted Drug Therapy - Rasha Saad Suliman; Sahar Saleh Alghamdi; Rizwan Ali; Dimah Aljatli; Norah Abdulaziz Aljammaz; Sarah Huwaizi; Rania Suliman; Khawla Mohammed Kahtani; Ghadeer M. Albadrani; Tlili Barhoumi; Abdulelah Altolayyan; Ishrat Rahman (MDPI AG, 2022)
Background: Myrrh extract is a well-known medicinal plant with significant therapeutic benefits attributed to the activity of its diverse metabolites. It has promising activity against cancer and inflammatory diseases, and could serve as a potential therapeutic alternative since most therapeutic agents have severe side effects that impair quality of life. Method: The current study identified the active metabolites from the myrrh resin methanolic extract. Then, the extracts were tested for in vitro anti-inflammatory and anti-cancer activity using cancer cell lines and Tamm-Horsfall Protein 1 (Thp-1)-like macrophage cell lines. Furthermore, using an in vivo rat model, the extracts' anti-inflammatory and wound-healing activity was investigated. In addition, in silico predictions of the myrrh constituents highlighted the pharmacokinetic properties, molecular targets, and safety profile, including cytochrome P 450 (CYP) inhibition and organ toxicity. Results: Nine secondary metabolites were identified, and computational predictions suggested a good absorption profile, anticancer, anti-inflammatory, and wound-healing effects. The myrrh extract had moderate cytotoxic activity against both HL60 and K562 leukemia cell lines and the KAIMRC1 breast cancer cell line. Myrrh caused a dose-dependent effect on macrophages to increase the reactive oxygen species (ROS) levels, promote their polarization to classically activated macrophages (M1) and alternatively activated macrophages (M2) phenotypes, and consequently induce apoptosis, highlighting its ability to modulate macrophage function, which could potentially aid in several desired therapeutic processes, including the resolution of inflammation, and autophagy which is an important aspect to consider in cancer treatment. The topical application of myrrh improved wound healing, with no delayed inflammatory response, and promoted complete re-epithelization of the skin, similar to the positive control. In conclusion, we provide evidence for the methanolic extract of myrrh having cytotoxic activity against cancer cells and anti-inflammatory wound-healing properties, which may be attributed to its role in modulating macrophage function. Furthermore, we suggest the active constituents responsible for these properties, which warrants further studies focusing on the precise roles of the active metabolites.